Emergency Generator Usage on Landing Craft Tank: A Brief Review - Danny Faturachman; Muhamad Padil De Manan; Karina A. Sulaeman (Techniques and Innovation in Engineering Research Vol. 1, 2022)
The Landing Craft Tank (LCT) is a type of attack landing craft for waterfront vessel tanks. Generally, LCT 415 Gross Tonnage (GT) ships are not equipped with emergency generators. Only ships with more than 500 GT are required to have an emergency generator package, according to Indonesia Classification Bureau or Biro Klasifikasi Indonesia (BKI) rules. However, in order to achieve a higher level of safety, the LCT 415 GT is outfitted with an emergency generator package installation. This generator serves as an electric power source for the ship’s compass when it is turned off. The goal of this research is to learn about the LCT 415 GT’s electrical power requirements in order to identify the required emergency generator package specifications and to provide an overview of the generator’s placement on the main deck. Emergency generator packages are organised to improve ship safety, crew safety, and cargo safety. LCT 415 GT ships required a total power of 29,9408 kW in an emergency. When extreme weather conditions occur, the basic package of emergency generator set selection is based on total emergency power in accordance with BKI regulations, as well as the generator safety engine package set.